2017
DOI: 10.1002/cssc.201701422
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Dissolution of Al Current Collectors in Unconventional Solvents for High Voltage Electrochemical Double‐Layer Capacitors

Abstract: This study investigated the anodic dissolution of Al current collectors in unconventional electrolytes for high voltage electrochemical double-layer capacitors (EDLCs) containing adiponitrile (ADN), 3-cyanopropionic acid methyl ester (CPAME), 2-methyl-glutaronitrile (2-MGN) as solvent, and tetraethylammonium tetrafluoroborate (Et NBF ) and tetraethylammonium bis(trifluoromethanesulfonyl)imide (Et NTFSI) as conductive salts. To have a comparison with the state-of-the-art electrolytes, the same salts were also u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…Chronoamperometric tests for nonscratched and scratched Cu electrodes at 4 V were conducted for a better understanding of the dynamics of the dissolution process. 24 Both nonscratched and scratched Cu electrodes exhibited abrupt increases in currents, as shown in Figure S1a,b. Moreover, the surface was seriously corroded after the polarization (Figure S1c,d).…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Chronoamperometric tests for nonscratched and scratched Cu electrodes at 4 V were conducted for a better understanding of the dynamics of the dissolution process. 24 Both nonscratched and scratched Cu electrodes exhibited abrupt increases in currents, as shown in Figure S1a,b. Moreover, the surface was seriously corroded after the polarization (Figure S1c,d).…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…Unexpectedly, this observation suggests passivation of the Cu metal surface in 0.5 M KFSI in EC/DEC electrolyte. Chronoamperometric tests for nonscratched and scratched Cu electrodes at 4 V were conducted for a better understanding of the dynamics of the dissolution process . Both nonscratched and scratched Cu electrodes exhibited abrupt increases in currents, as shown in Figure S1a,b.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that the use of alternative conductive salts in conventional and unconventional solvents enables the realization of EDLCs with operative voltages of >3.0 V. Among the salts proposed so for, those based on the anion bis­(trifluoromethanesulfonyl)­imide (TFSI) are considered of high interest, and they have been widely investigated in the past several years. The use of this anion might lead to the realization of salt with a high electrochemical stability, good thermal stability, and good solubility in water, organic solvents, and ionic liquids. ,, The main drawback associated with the use of TFSI-based salts is related to their limited ability to prevent the anodic dissolution of the aluminum (Al) current collectors. ,, This latter aspect has been the subject of several investigations, and it has been shown that the solubility of the complex aluminum bis­(trifluoromethanesulfonyl)­imide [Al­(TFSI) 3 ] in the electrolyte is what determines Al anodic dissolution. More precisely, the higher the solubility of Al­(TFSI) 3 in the electrolyte, the higher the magnitude of the dissolution process. , …”
Section: Introductionmentioning
confidence: 99%
“…The use of this anion might lead to the realization of salt with a high electrochemical stability, good thermal stability, and good solubility in water, organic solvents, and ionic liquids. ,, The main drawback associated with the use of TFSI-based salts is related to their limited ability to prevent the anodic dissolution of the aluminum (Al) current collectors. ,, This latter aspect has been the subject of several investigations, and it has been shown that the solubility of the complex aluminum bis­(trifluoromethanesulfonyl)­imide [Al­(TFSI) 3 ] in the electrolyte is what determines Al anodic dissolution. More precisely, the higher the solubility of Al­(TFSI) 3 in the electrolyte, the higher the magnitude of the dissolution process. , …”
Section: Introductionmentioning
confidence: 99%
“…In the last years, several nitrile-based electrolytes such as glutaronitrile (GTN) [49][50][51], adiponitrile (ADN) [51][52][53][54][55][56], butyronitrile (BTN) [54,55], and 2-methylglutaronitrile (2-MGN) [51], have been investigated as replacements of ACN. These solvents have been used in combi nation with Et 4 NBF 4 as well as other conducting salts [49][50][51][52][53][54][55][56][57]. They typically display lower ionic conductivities compared to ACN-based electrolyte.…”
Section: Alternative Electrolytes For Edlcsmentioning
confidence: 99%